2022
DOI: 10.1128/mra.00137-22
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Stenotrophomonas maltophilia Podophage Ptah

Abstract: Stenotrophomonas maltophilia is an opportunistic pathogen demonstrating increasing drug resistance. Here, the genome of the T7-like S. maltophilia podophage Ptah is described. Its 42,593-bp genome is closely related to previously reported T7-like S. maltophilia podophages, including phage Ponderosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The structure of the receptor-binding proteins of StenM_174 was predicted using AlphaFold2. A comparative analysis of the genome showed that the Stenotrophomonas phage StenM_174, along with the phages Ponderosa [ 24 ], Pepon [ 25 ], Ptah [ 26 ], and TS-10 (GenBank ID OK018136), can be members of the new putative genus Ponderosavirus within the Autographiviridae family. In addition, the analyzed data suggest a new subfamily within this family.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the receptor-binding proteins of StenM_174 was predicted using AlphaFold2. A comparative analysis of the genome showed that the Stenotrophomonas phage StenM_174, along with the phages Ponderosa [ 24 ], Pepon [ 25 ], Ptah [ 26 ], and TS-10 (GenBank ID OK018136), can be members of the new putative genus Ponderosavirus within the Autographiviridae family. In addition, the analyzed data suggest a new subfamily within this family.…”
Section: Introductionmentioning
confidence: 99%